On the Afterlives of Daphne Du Maurier’s Rebecca: Spinoffs and Transfictions - Armelle Parey (Revue LISA)
Daphne Du Maurier’s Rebecca is one of these novels that are regularly submitted to rewriting and expansion. If the process “preserves the traditional canon’s centrality” (as Jeremy Rosen says about minor character elaborations), it also participates in the critical reassessment of the source text as it throws a new light on it. This article discusses very diverse transfictions based on Du Maurier’s novel and examines the workings of the various narrative strategies adopted to reactivate the well-known novel. This will enable us to underline the elements, traits or characteristics of Rebecca that are picked upon – and which ensure Du Maurier’s novel an afterlife – and how these various revisions and/or expansions engage with the source text. While Antonia Fraser’s “Rebecca’s Story” (1976) is a coquel enabling a first-person account by Rebecca of her marriage, Rose Tremain’s “The Housekeeper” (2014) changes diegetic level as it portrays the young Du Maurier and gives an account of the inspiration behind Rebecca by the character misrepresented as Mrs. Danvers. Other texts under study are Susan Hill’s Mrs. de Winter (1993) and Sally Beauman’s Rebecca’s Tale (2001), which offer narrative and temporal expansions, and finally Lisa Gabriele’s The Winters (2018), a transposition of the plot and its characters to contemporary America.